(untitled) (International Journal of Engineering and Computer Science, 2016)
India’s Public Distribution System (PDS) is the largest retail system in the world. System of Public Distribution provides a ration card issued under an order or authority of the State Government for the buy of essential consumer materials like rice, wheat, kerosene and oil. State Government issues distinctive ration identity cards like yellow ration card, saffron (orange) ration card, and white ration card depending on family annual income. The consumer material is feeding to ration card holders in the first week of every month by ration shop keeper. System of Public Distribution is one of the widely disputable issues that involve malpractice. The manuscript intervention in weighing of the materials leads to incorrect measurements and/or it may happen, the ration shop owner illegally uses consumer materials (Rice, Wheat, Kerosen) without previously knowledge of ration card holders. The proposed system aids to power control malpractices which are present in ration shop by superseding manual work with automatic system based on RFID. Every consumer i.e. family head provided RFID radio frequency identification card which acts as ration identity card. The RFID card has unique (rival) identification number. The consumer scans the card on RFID radio frequency identification reader which is faced with microcontroller kept at ration shop. Once consumer is validated by details, the system shows customer’s product and cost. Based on material chosen by consumer, appropriate correct circuitry will be activated and consumer gets material. The proposed RFID based automatic ration shop system would bring transparency appropriate in public distribution system and become aids helpful to prevent malpractices.